2D/2D Bi2Se3/SnSe2 heterostructure with rapid NO2 gas detection - Yi, Shuangshuang; Chen, Cunguang; Yu, Meiling; Hao, Juanjuan; Wang, You (Frontiers in Chemistry, 2024)
Heterostructure engineering is crucial for enhancing gas sensing performance. However, achieving rapid response for room-temperature NO2 sensing through rational heterostructure design remains a challenge. In this study, a Bi2Se3/SnSe2 2D/2D heterostructure was synthesized by hydrothermal method for the rapid detection of NO2 at room temperature. By combining Bi2Se3 nanosheets with SnSe2 nanosheets, the Bi2Se3/SnSe2 sensor demonstrated and the lowest detection limit for NO2 a short response time (15 s) to 10 ppm NO2 at room temperature, reaches 25 ppb. Furthermore the sensor demonstrates significantly larger response to NO2 than to other interfering gases, including 10 ppm NO2, H2S, NH3, CH4, CO, and SO2,demonstrating its outstanding selectivity. And we discuss the mechanism of related performance enhancement.